Corticotropin-releasing hormone expression is the major target for glucocorticoid feedback-control at the hypothalamic level - Kretz, Oliver; Reichardt, Holger Michael; Schütz, Günther (Brain research, 1999)
Glucocorticoid production is controlled via the hypothalamo-pituitary–adrenal (HPA) axis by a negative feedback mechanism involving the glucocorticoid receptor (GR). A major site of regulation is the hypothalamus, where the GR is thought to repress the expression of genes such as corticotropin-releasing hormone (CRH) and arginine–vasopressin (AVP). To define the role of the GR in this feedback loop in more detail, the content of CRH, AVP and neurophysin in the median eminence of mice carrying a targeted disruption of the GR gene was studied using immunohistochemistry. GR-deficient mice were found to contain five times more CRH in the median eminence than wild-type littermates. In contrast, no significant change in the content of AVP was observed in the outer layer of the median eminence and neurophysin was also only moderately increased. Our studies suggest that, at the hypothalamic level, CRH synthesis is the major target for feedback control by the GR and that transcriptional control of AVP and neurophysin plays only a supportive role in this process.